Penerapan QR Code Untuk Sistem Absensi Siswa SMP Berbasis Web - Elin Herlina; Taufik Hidayatulloh (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2017)
QR Code is a type of two-dimensional bar code in the form developed by Denso Wave, a division of Denso Co. Corporation, a perudahaan in Japan, which was published in 1994. Barcode is a symbol marking the real object made of sticks pattern of black and white in order manage computer is easy to recognize a good student attendance data is needed to be able to provide ease in generating student attendance data and is one of the important factors in managing a good attendance data. Management of student attendance by using a QR Code-based Web is an application that will be built in